Implementation of Learning Models Inquiry Guided To Ability Thinking HOTS Students in Science Lessons Care Environment in Grade IV of Masadian Public Elementary School Subdistrict Sombori Archipelago Regency Morowali - Nurdarmayanti, Ni Ketut; Hasan; Nuraedah (Kirana Publisher (KNPub), 2025)
Education is effort aware For develop source Power human resources (HR) through activity learning . As the learning process progresses , so does the learning process . Learning is essentially is provide environment that facilitates the learning process student with facilitate growth and development its potential . Formulation problem research what are the teacher 's steps in implementing learning models Inquiry Guided in class IV of Masadian State Elementary School , how Integrating Learning Models Inquiry Guided with Caring Science Lessons The environment in class IV of Masadian State Elementary School , how is it? implementation of learning models Inquiry Guided to ability HOTS thinking Students Class IV in Science Lessons Caring Environment in class IV of Masadian State Elementary School . Research purposes For Integrating Learning Models Inquiry Guided with ability think HOTS on Caring Science Lessons The environment of science in class IV of Masadian State Elementary School . The research method used by the researcher namely the qualitative descriptive research method . The results of the research on the learning model inquiry guided program carried out in class IV of Masadian State Elementary School is a learning model that focuses on the use of thinking critical and analytical For can find solution from problems faced . methods​ inquiry guided involving learning in situation child educate given equal opportunity​ For do experiment or test Alone in the situation that has prepared . Conclusion of the study The steps taken by teachers in Implementing Learning Models Inquiry Supervised in class IV of Masadian State Elementary School , Steps learning carried out by teachers in class that is do discussion given by the science and science subject teacher the discussion Using Learning Models Inquiry Guided with A learning model that invites student For find Alone knowledge through investigation , observation , or experiment , with guidance or directions from the teacher.